2014 IEEE Globecom Workshops (GC Wkshps) 2014
DOI: 10.1109/glocomw.2014.7063447
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of hardware impairments on massive MIMO

Abstract: Massive multi-user (MU) multiple-input multipleoutput (MIMO) systems are one possible key technology for next generation wireless communication systems. Claims have been made that massive MU-MIMO will increase both the radiated energy efficiency as well as the sum-rate capacity by orders of magnitude, because of the high transmit directivity. However, due to the very large number of transceivers needed at each basestation (BS), a successful implementation of massive MU-MIMO will be contingent on of the availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
116
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 14 publications
1
116
0
Order By: Relevance
“…Based on this model, it was concluded that massive MU-MIMO exhibits a certain degree of robustness against hardware impairments. While the underlying Gaussian impairment model was demonstrated to be accurate for a diverse set of residual RF impairments [5], [6], this model is a poor match for coarse quantization, which causes deterministic distortions that areby nature-dependent on the transmit signal.…”
Section: B Relevant Prior Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this model, it was concluded that massive MU-MIMO exhibits a certain degree of robustness against hardware impairments. While the underlying Gaussian impairment model was demonstrated to be accurate for a diverse set of residual RF impairments [5], [6], this model is a poor match for coarse quantization, which causes deterministic distortions that areby nature-dependent on the transmit signal.…”
Section: B Relevant Prior Artmentioning
confidence: 99%
“…5 This holds provided that the priors are product distributions, i.e., that f (h) = W w=1 f (hw) and that p(s) = W w=1 p(sw). 6 Our framework enables also the use of multi-antenna user equipments. In this case, forward error correction and channel decoding can be performed over the multiple antennas.…”
Section: A Quantized Mimo-ofdm System Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the total power efficiency of the transmitter in the LSAS regime is significantly higher than the total power efficiency in classical design. In [35], authors examined the effects of hardware impairments on a LSAS single-cell system. The simulations were performed using simplified, well-established statistical hardware impairment models as well as more sophisticated and realistic models based upon measurements and electromagnetic antenna array simulations.…”
Section: Rf Componentmentioning
confidence: 99%
“…There are several studies related to the RF component of LSAS [34][35][36]. In [34], a novel single-RF LSAS transmitter was presented.…”
Section: Rf Componentmentioning
confidence: 99%